Effect of Product Enhancement Type on Replacement and Purchase Preference of Consumers - Hsu, Y (KnE Social Sciences, 2018)
In the fiercely competitive market of information electronics, each brand constantly releases newly enhanced products. Faced with a new product, consumers often compare it with the old product; they evaluate the remaining mental book value (MBV) of the old product or assess the difference in enjoyment (DIE) between the new and old products. Regarding replacement and purchase (RAP) behaviors, various types of consumers can exhibit dissimilar behaviors and preferences. This study employs notebook computers as sample products because these products are innovative, released in product series, and form a competitive market. A questionnaire was completed by 400 participants. The RAP preference of the participants when confronted with various product enhancement types (PETs) was determined with regard to two types of self-construal and two types of self-regulation. The mediating variables were MBV and DIE of new and old products. The results are as follows: (1) The participants are more likely to exhibit RAP behaviors for products with general enhancement (GE). (2) When the PET is GE, the participants with promotion focus—a type of self-regulation—tend to exhibit RAP behaviors. (3) When the PET is focused enhancement, the participants with prevention focus tend to exhibit RAP behaviors. The study results reveal how enterprises should develop strategies for product innovation as well as how they should fix product defects. The study results also indicate that enterprises can, according to consumer types and purchasing preferences, construct appropriate marketing strategies to increase product design quality. Keywords: information electronics, product enhancement type, self-construal, selfregulatory